Employees’ shariah provident fund in Malaysia: a juristic analysis صندوق التقاعد الشرعي للعمال بماليزيا: تحليل فقهي - Hanafi, Khalil Husni; Sawari, Mohd Fuad; Dollah, Nafi@Hanafi (IIUM Press, 2019)
The purpose of this article is to analyze the experience of the Employees’ Provident Fund or EPF in the management of the Shariah Fund and the jurisprudential adaptation of its activities and investments. This article selects the EPF in Malaysia as a model for analysis as a successful financial project. This article uses both inductive and analytical approaches to achieve its objectives. Malaysia's Shariah Retirement Savings Fund for workers needs to develop Shariah-compliant investment methods to achieve the objective of investing the savings of contributing members with a good financial return so that the members’ financial assets in the fund will increase. The article reveals that the Malaysian Workers’ Provident Pension Fund was developed on the wakālah (agency) contract which matches the nature of the fund's activities with its rich, flexible and secure features.